Challenges of Irrigation Water Management on Smallholder Schemes: Case Study in Dembecha Woreda, Northwest Ethiopia - Anteneh, Balager; Belay, Mehretie (Ethiopian Journal of Social Sciences, 2020)
Smallholder irrigation has enormous potential to improve the incomes of poor rural households in developing countries like Ethiopia. However, numerous problems constrain irrigated crop production and irrigation water management efforts in many areas. In light of this, a survey was conducted with the objective of assessing the challenges of irrigation water management over smallholder schemes, in Dembecha Woreda (District), in the northwestern highlands of Ethiopia. Data were gathered through key informant interviews, group discussions, field observations and a questionnaire survey of 118 households. The data gathered were then analyzed using descriptive statistics; independent sample T-test and the Chi-square test. The results showed that irrigation water in the study area was distributed using rotation turns and the process was managed by an elected body of water users called irrigation water use committees. Over 63% of the respondents faced water shortages on their farms. Loss of water through seepage, poor coordination of water distribution by water use committees, water theft problems, water shortage at tail-end irrigators, absence of enforcing rules, water use conflicts, and rotation turn abuses were identified as major challenges of irrigation water management in the study areas. Hence, it is suggested that farmers be encouraged to harvest rain and underground water to stabilize water shortages and be provided with water management trainings.